MODULATORS OF THE BIOSYNTHESIS AND OF THE MECHANISM OF ACTION OF ETHYLENO ON THE GROWTH IN VITRO OF APPLE MARUBAKAIDOS STOCK - MEDEIRO, Sandra Aparecida (Scientia Agraria, 2002)
Lids used in culture vessels usually constrain gas exchange between the inner and outer vessels atmosphere. This constrain typically leads to a considerable raise in the internal ethylene concentration which often cause reduction on the multiplication rate for in vitro-grown tissues. Reduction on the internal ethylene concentration through the inhibition of the growth regulator biosynthesis or signal transduction pathway has increased multiplication rate (MR) in various systems. This increase on MR reduce micropropagation cost and time. This study aimed to increase in vitro MR for the Marubakaido apple rootstock through the use of compounds known to inhibit ethylene biosynthesis or signal transduction pathway. Nodal segments of a clone of Malus prunifolia cv Marubakaido were grown in MS (MURASHIGE e SKOOG,1962) culture medium supplemented with 2,22 µM benzylaminopurine. Explants were kept in growth room at 27 ± 2 ºC, 16-hours photoperiod, photosynthetic photon flux density (PPFD) of 40 mmol.m-2.s-1, at the culture level, and relative humidity at 75 ± 5%. AVG (L-a-(2-aminoethoxyvinyl)- glycine), AIB (a-aminoisobutyric acid), CoCl 2 (cobalt dichlorate), and brassinosteroids 28-HCTS (homoethylcastasterone) and 5F-HCTS (28- homoethil-5-fluor-castasterone), inhibitors of ethylene biosynthesis, and STS (silver thiosulphate) and 1-MCP (1-methylcyclopropane), well known inhibitors of the ethylene sinal transduction pathway were used in this study through the addition to the culture vessels internal atmosphere, in the case of 1-MCP, through leaf application, in the case of brassinosteroids, or through the addition to the culture media, in the case of the other mentioned chemicals. Evaluation consisted of measurements of shoot length and their hierarchy distribution, number of shoots measuring 1,5 cm or more in length, number of shoots measuring less than 1,5 cm in length, also with their hierarchy distribution, and multiplication rate (number of shoot apices and nodal segments useful for micropropagation purposes). A 74% increase on the number of main branches < 1,5 cm was related to the presence of AVG at 5 µM in the culture medium. No significant change for any of the measured parameters was found for shoots grown in CoCl 2 or AIB-containing media. Reduction on MR was found for all of the 1-MCP and STS treatments. Among the brassinosteroids, only 5F-HCTS induced significant changes on shoot growth dynamics. An 83% increase on MR was related to the dose of 1 µg.shoot . This increase on MR was related to a raise of 52% on the number of lateral branches ³ 1,5 cm. Concluding, the 5F-HCTS shows potential to be used on the improvement of the in vitro propagation technique for the Marubakaido apple rootstock.